Smart contract as a tool for digital transformation of penitentiary system economy - A. M. Chernyaev (Вестник университета, 2023)
The Russian penitentiary system is a large diversified industry with a total annual output of goods, works and services worth more than 30 billion rubles. The process of integrating such a manufacturer into the national digital economic system requires a special set of tools, one of which, in the author’s opinion, is a smart contract. The object of the study is the sphere of labor adaptation of convicts, subject is digital tools to improve efficiency of production processes and relations in the penitentiary system. The article studies the use of smart contracts as one of the promising directions for improving economic activity of correctional institutions and optimizing the contracting system. As a result of the study, the author concluded that it is advisable to develop smart contracts as a tool to strengthen and develop economic potential of the penitentiary system, and also suggested possible directions of its practical application.